Evidence for Feasibility of Fetal Trophoblastic Cell-Based Noninvasive Prenatal Testing. Issue 1 (January 2017) - Breman, Amy M.; Chow, Jennifer C.; U'Ren, Lance; Normand, Elizabeth A.; Qdaisat, Sadeem; Zhao, Li; Henke, David M.; Chen, Rui; Shaw, Chad A.; Jackson, Laird; Yang, Yaping; Vossaert, Liesbeth; et al.
Abstract : (Abstracted from Prenat Diagn 2016;36:1–11) The potential use of fetal cells in maternal blood for prenatal diagnosis has been a promising technology for decades. Several strategies have been tried and tested for recovering fetal cells, although they are inconsistent and not reproducible.